(untitled) (Bangladesh Journal of Agricultural Research, 2019)
Effect of soil incorporated Tricho-compost @ 5.5 t/ha (T1) and foliar spray of Tricho-leachate @ 4 ml/l at 15 days interval (T2) each alone or in combination (T3) were evaluated on mortality of strawberry plant in the maintenance nursery and growth and development of daughter plants in the main filed. Traditional practice of maintenance of plants in the nursery bed was considered as control (T4). The study was conducted at the Regional Horticultural Research Station, Bangladesh Agricultural Research Institute, Sibpur, Narsingdi, during June 2015 to March 2016 and BARI Strawberry-1 was used in the study. The lowest mortality (6.67%) in the nursery bed was recorded in saplings treated by T3, while the highest mortality (16.67%) was recorded in the control plot (T4) and the trend was also followed in the main field. Days to flowering (47.67) and days to first harvest (71.67) of saplings treated by T1 were earlier as compared to that of saplings of control plot (60.67 and 93.33 respectively). The maximum harvest duration was recorded in saplings treated by Tricho-compost (74 days) followed by T2 (61.33 days) and T3 (59.33 days). Total Soluble Solid (TSS) of fruits were also improved when the plants were treated by Tricho-products. The maximum fruit yield (621.68g per plant) was recorded from T3; while, the lowest yield (396.83g per plant) was recorded in saplings treated by Tricho-leachate @ 4ml/l. Bangladesh J. Agril. Res. 44(2): 195-201, June 2019